THE ROLE OF TEACHER PEDAGOGIC COMPETENCE IN ENHANCING ISLAMIC RELIGIOUS EDUCATION LEARNING MOTIVATION AMONG FIFTH-GRADE STUDENTS AT SDN MERGOLANGU, KALIBAWANG, WONOSOBO - Surwaningsih; Hidayatu Munawaroh; M. Yusuf Amin Nugroho (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
This study aims to determine the role of the Islamic Religious Education teacher's pedagogical competence, as well as the factors supporting and hindering the teacher's efforts to boost the Islamic Religious Education learning motivation of fifth-grade students at SD Negeri Mergolangu. The study employs a qualitative approach and a descriptive research design. It was conducted at SDN Mergolangu, Wonosobo Regency. Data collection methods included interviews, observation, and documentation, while data analysis involved data reduction, data verification, and drawing conclusions. The subjects of the study were the school principal and the Islamic Religious Education teacher. The findings conclude that the roles of the Islamic Religious Education teacher's pedagogical competence in instruction are: 1) demonstrator, 2) facilitator, 3) mediator, 4) classroom manager, and 5) evaluator. Thus, the teacher's role facilitates student learning, enabling optimal student development. Factors hindering the teacher's pedagogical competence in boosting learning motivation among fifth-grade students at SD Negeri Mergolangu include a lack of student interest in learning and insufficient parental guidance and attention regarding their children's education. Supporting factors include the teacher communicating learning objectives, awarding grades for active participation, offering praise, and administering disciplinary measures to students who commit errors